Pengaruh penggunaan bahan ajar fisika terintegrasi konten nilai kecerdasan sosial pada materi gerak parabola dan gerak melingkar terhadap pencapaian kompetensi siswa kelas X SMA 13 Padang - Maulana Aflah; Maulana Aflah; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2019)
The achievement of students physics competencies is expected to be achieved comprehensively. In order to achieve competencies that are expected to be needed teaching material that contain all competencies, as well as learning models that can increase student activity. This study aims to determine the effect of the use of physics teaching materials integrated intelligence content on parabolic motion and circular motion towards the achievement of class X student competency in SMA 13 Padang. This type of research is Quasi Experimental with research design The Randomize Posttest Only Control Group. Determination of sample classes using purposive sampling techniques. The research data include data on the achievement of competencies in social attitudes, knowledge, and skills. The competency data obtained will be analyzed using descriptive statistics on the three competencies, the similarity test two on the knowledge competency, and the regression test on the three competencies. Based on the results of the analysis that has been done the average value in each competency in the experimental class is higher than the control class. The use of integrated physics teaching materials social intelligence influences the competence of social attitudes by 73%. The knowledge competencies of both sample classes are normally distributed and homogeneous, so the t test is done with the results of th= 4.63 and t table = 1.76. From the t test, it is obtained th> tt where th is not in the reception area Ho so that Hi is accepted which means there are significant differences between the experimental class and the control class. In addition to the differences, integrated physics teaching material content of social intelligence values has an influence of 68%. Achievement of skills competencies using integrated physics teaching materials content of social intelligence has an influence of 67%. These results indicate that there is a significant effect on the achievement of student competence.